Absolute Stability of a Class of Nonlinear Singular Systems with Time Delay - Hong-Bing Zeng; Gang Chen; Shen-Ping Xiao (Abstract and Applied Analysis)
This paper deals with the absolute stability for a class of nonlinear singular systems with time delay. By employing a new Lyapunov-Krasovskii functional with the idea of partitioning delay length, improved delay-dependent stability criteria are established. The resulting condition is formulated in terms of linear matrix inequalities (LMIs), which is easy to be verified by exiting LMI optimization algorithms. A numerical example is given to show the effectiveness of the proposed technique and its improvements over the existing results.